Influence of egg storage time, position and turning on egg weight loss, embryonic mortality and hatching traits in chukar partridge (Alectoris chukar). Issue 1 (31st December 2022) - Çam, Mustafa; Kaya, Zahit K.; Güler, Serdar; Harman, Halil; Kırıkçı, Kemal
Abstract: The aim of the study was to evaluate the effect of storage length (7, 14, 21 and 28 days), turning frequency (0, 1 and 24 times per day) and egg position (pointed end up, blunt end up and horizontal) on egg weight loss during storage and incubation; hatchling chick weight, incubation length and hatchability results in 56-week-old chukar partridges ( Alectoris chukar ). A total of 1800 daily collected eggs was assigned to 36 subgroups (4 × 3 × 3 experimental design) consisting of 50 eggs for each subgroup. Progressive decrease in egg weights and increase in egg weight loss during storage was observed with the lengthening of storage period ( p < .001). Prominent effects were observed in total egg weight loss rate and incubation length when the eggs were stored more than 21 days ( p < .001). The highest hatchling chick weights were observed in horizontal eggs stored for 7 days ( p < .001). Most indices of hatching results showed detrimental effects when turning wasn't applied and the eggs were stored with the position of blunt end up. General recommendations from the hatching results showed that chukar eggs can be stored up to 21 days of storage length irrespective of turning and egg position. If the chukar eggs are to be stored more than 21 days, turning should be implemented and the eggs should be placed with the position of pointed end up for optimum hatching results. HIGHLIGHTS: Due to their chicks' valuability, partridge eggs are aimed to be incubated. In addition, scientific studies of egg hatching assessment under different conditions during storage period are lacking. For these reasons, the study was carried out to determine optimum conditions of storage in chukar eggs. The present results revealed that storing the chukar eggs with the position of pointed end up till 21st days improves the quality of the eggs. If the storage length is to exceed 21 days, the eggs should be turned at least once a day and placed with the position of pointed end up.